PENGARUH MEDIA PEMBELAJARAN BERBASIS WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS III DI SD INPRES HARTACO INDAH KOTA MAKASSAR: Penelitian Kuantitatif pra-eksperimen - Saskia; Ashar; Syamsuriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The effect of Wordwall-based learning media on the learning outcomes of grade III students at SD Inpres Hartaco Indah, Makassar City on the material of game activities and water sports. The approach used is quantitative with a pre-experimental design of the One Group Pretest-Posttest Design type. The sample in this study was 30 students. The results of the study showed an increase in learning outcomes after Wordwall-based media. This can be seen from the increase in the average value from 62.16 in the pretest to 81.66 in the posttest, as well as a decrease in the standard deviation from 12.08 to 5.92, which indicates an increase in the consistency of student learning outcomes. The normality test shows that the data is normally distributed. Meanwhile, the results of the Paired Sample t-Test produced a significance value of 0.001 <0.05, indicating a significant difference between the pretest and posttest results. The questionnaire data also showed that students responded very positively to Wordwall-based media in learning. Therefore, it can be concluded that Wordwall-based learning media has a significant effect on student learning outcomes, and also helps improve understanding and interest in learning, especially in PJOK learning.